Doing Business report and real estate transfers: Far better with legal controls and notarial guarantee : legal empowerment is a key factor at global level, especially in developing economies of Africa, Asia and Latin America - Antonio Cappiello (African Governance and Development Institute (AGDI), 2020)
In the last years, the Doing Business (DB) Project of the World Bank - recommending reforms aiming at removing obstacles that may produce increase of time, cost and procedures - had a significant influence on policies making. A recent DB research note (2019) also proposed to make optional use of professionals (including notaries) in operations such as real estate transfer in order to increase the efficiency of the country system. Nevertheless, the aggregate assessment focusing on the data of the 190 economies analysed by DB Registering property indicator and sub-indicators (synthetic RP indicators as well as all sub-indicators), shows that countries using notaries in the real estate transactions are the most efficient. Since the evidence emerging from DB data shows that the control of the State delegates produces (besides legal security and reliability) better efficiency, the overall logic of DB global reforms in the property transfer may be reconsidered. As an alternative to the tout court idea of eliminating every kind of intermediation, it would be reasonable to consider the tangible empirical effects produced by a system and to involve State officers in establishing best strategy for efficiency, keeping at the same time the guarantee for the society and the vulnerable agents.
Keywords: 330; doing business; professional services; real estate transfers; performanceindicators; rank methodology